Tax and Occupancy of Business Properties: Theory and Evidence from UK Business Rates - Ben Lockwood; Martin Simmler; Eddy H.F. Tam (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the impact of commercial property taxation on vacancy rates and rents in the UK, using a new data-set, and exploiting exogenous variations in property tax rates from reliefs in the UK system: small business rate relief (SBRR), retail relief and empty property relief. We estimate that the retail relief reduces vacancies by 85%, and SBRR relief by up to 49%, while empty property exemption increases them by up to 89%. The effect of retail relief on clusters of urban properties (the "High St") is no different to its overall effect. SBRR increases (decreases) the likelihood that a property is occupied by a small (large) business. We also use data on asking prices for rental properties to study the effect of reliefs on rental rates. Rental rates move in the opposite direction to vacancy rates, except in the case of empty property relief. All these findings are consistent with a novel model of directed search in the commercial property market, also presented in the paper.
Keywords: H25; H32; R30; R38; 330; commercial property; vacancy; occupancy; property taxation